A Recurrent Misdiagnosed and Maltreated Case of Keratosis Obturans - Hamoud Alarouj; Faisal AlObaid; Abdulmohsen K. AlBader; Mahmoud A. K. Ebrahim (Case Reports in Otolaryngology)
Keratosis obturans is an obscure entity characterized by accumulation of desquamated keratinous material in the bony portion of the external auditory canal. Patients with this condition typically present with severe otalgia, conductive hearing loss, and global widening of the external auditory canal. We present a case of keratosis obturans that was misdiagnosed as impacted wax. The case was diagnosed and managed by microscope-guided examination with the patient under general anesthesia.